An Object in the Interior by the Example of St. Petersburg Mansions of the Late 19th — Early 20th Century - Dolgova, Anastasia I. (Actual Problems of Theory and History of Art, 2018)
The purpose of the research is the identification of some common trends in Art Nouveau interior and the examination of the theme “an object in the interior” by the example of St. Petersburg mansions built in the late 19th — beginning of 20th century. Classical Jean Baudrillard’s work “The System of Objects” has been used as a theoretical basis.The examination of interiors of Art Nouveau private houses in this context appears particularly productive.Things and objects proved to be extremely important for the new style. At this point, the search for ways to modernize art has begun, and through these objects the artists tried to introduce art into everyday life of every person.The article addresses the issues of the relationship between things/objects and space, the opposition between modern and traditional interiors, the selection of objects that fill them, the subjectivity of Art Nouveau interiors, and the mythologization of individual items.
Keywords: city residences; mansions; St. Petersburg Art Nouveau; Art Nouveau architecture; interior decoration; furniture; applied arts; objects